Expression of Cultural Views through Animal Images in Korean and Uzbek Proverbs - Xikmatullayeva Durdona (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This article provides a comparative linguacultural analysis of animal imagery utilized in Korean and Uzbek proverbs. In the course of the research, figurative proverbs in the Korean language were selected and subjected to a comparative analysis with semantically equivalent Uzbek proverbs. The animal images embedded in the proverbs and the metaphorical meanings expressed through them are thoroughly investigated to identify similarities and distinctive features. Specifically, using the examples of tiger, wolf, monkey, horse, fish, cat, and bird imagery, the study explains how the same core concept is manifested through diverse semantic means within different cultural environments.